Synthetic harbour porpoise (Phocoena phocoena) communication signals emitted by acoustic alerting device (Porpoise ALert, PAL) significantly reduce their bycatch in western Baltic gillnet fisheries - Chladek, Jerome-Christoph; Culik, Boris M.; Kindt-Larsen, Lotte; Moesgaard Albertsen, Christoffer; Dorrien, Christian von (Fisheries Research, 2020)
Gillnet fisheries are one of the main anthropogenic causes of harbour porpoise (Phocoena phocoena L., 1758) mortality in the Baltic Sea. A new kind of acoustic alerting device (Porpoise ALert, PAL) was tested in commercial gillnet fisheries in the western Baltic. PAL emits 133 kHz synthetic harbour porpoise communication signals, unlike conventional acoustic deterrent devices (pingers), which emit artificial noise. Trials were undertaken by three commercial gillnet vessels conducting 778 trips during standard fishing operations from 2014 to 2016. In all, 1120 PAL-equipped net strings were tested against 1529 simultaneously set control strings with no devices. We tested two versions of the PAL (v1 and v2) consecutively. These were spaced <=210 m apart on the gillnet floatlines, with all devices pointing in the same direction to ensure complete acoustic coverage of the strings. Two vessels fished in Kiel Bight and around Fehmarn Island in German waters, and the third vessel fished in the Øresund, in inner Danish waters. Overall, 18 harbour porpoises were bycaught in control strings (mean 0.01 ± 0.1/haul), and five harbour porpoises were taken as bycatch in strings equipped with PALs (0.004 ± 0.07/haul). The number of net string bycatches was analysed using a generalised linear mixed model (GLMM). The model applied to all observations revealed that the expected bycatch was significantly influenced by PAL deployment (p < 0.05), decreasing the expected bycatch by 64.9 % (95 % confidence interval (CI): 8.7–88.7 %). PAL effectiveness was also increased by reducing device spacing to <=200 m (16 bycatches in control, three in PAL strings; mean bycatch reduction 79.7 %). Additional model cases were applied to the data and are discussed. We conclude that, with this specific communication signal, PAL can significantly reduce harbour porpoise bycatch in gillnets deployed in the western Baltic Sea, thus reconciling anthropogenic activities with protection of the marine environment.